The Atis of Boracay living in the intersections of class, gender and ethnicity - Matorres, Dane Erlo C.
Indigenous people remain to be the most disadvantaged sector of our population. The economic, social, political, and environmental changes that shaped our present society greatly impacted their lives. Significantly, studies on indigenous groups to day explored the asymmetric effects of changes to women and men. This development is important in the Philippines since the country scores relatively high in current global equality indices and it has the most progressive law concerning indigenous groups with the passing of indigenous Peoples Rights Act in 1997. This qualitative and descriptive case study explored the present gender division of labor among the Atis in Brgy. Manoc-Manoc, Boracay Island, Malay, Aklan. Guided by theories and acculturation strategies, gender division o9f labor, and intersectionality, key informant interviews were conducted with 21 respondents. Content analysis of pertinent documents and one focus group discussion was also carried out with 14 Ati participant5s. Study results revealed that women are multiple burdened with domestic chores. Child rearing, wage work, and community obligations. However, sexism is not strong among the Atis as women access to resources is not restricted and they hold leadership positions in the community. Economic marginalization and uncertainty of land ownership are two of the biggest problems confronting the Atis. These issues are compounded by interactions of class, gender, and ethnicity in the context of contested ancestral land and capitalistic industry mainly define the present condition of the Atis.